EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT PADA PT. JUMBO POWER INTERNATIONAL - Viktorina, Kintan; Sabijono, Harijanto; Pinatik, Sherly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Credit sales accounting information system involves several sections that handle the field of sales. Such as sales, credit, warehouse, shipping, billing and accounting. If every part does not work properly in accordance with the prevailing system, then it tends to make mistakes, both the sale and recording activities. This study aims to evaluate the application of credit sales accounting information systems at PT. Jumbo Power International is in accordance with the concept or not. The analytical method used in this thesis research is a descriptive method in which the purpose of each data collected is analyzed and drawn a conclusion. The research results obtained that the accounting information system for credit sales at PT. Jumbo Power International is in accordance with the concepts that form the basis of comparison, although there are still multiple tasks.